Insect-specific RNA viruses detection in Field-Caught Aedes aegypti mosquitoes from Argentina using NGS technology - Ripoll, Lucas (2025)
Mosquitoes are the primary vectors of arthropod-borne pathogens. Aedes aegypti is one of the most widespread mosquito species worldwide, responsible for transmitting diseases such as Dengue, Zika, and Chikungunya, among other medically significant viruses. Characterizing the array of viruses circulating in mosquitoes, particularly in Aedes aegypti, is a crucial tool for detecting and developing novel strategies to prevent arbovirus outbreaks. In this study, we address the implementation of a sequencing and analysis pipeline based on the Oxford Nanopore Technologies MinION Mk1b system, for arboviral detection in field-caught mosquitoes from Argentina. Full genome of Humaita Tubiacanga Virus (HTV), Phasi Charoen-like Phasivirus (PCLV), Aedes aegypti totivirus (AaeTV) has been sequenced in three distinct regions of Argentina comprising Buenos Aires province, Santa Fe province and the northern province of Salta. Viral sequences enriched by SISPA and coupled with Nanopore sequencing can be a useful tool for viral surveillance, not only for detecting viruses that have a high impact on human and animal health, but also for detecting insect-specific viruses that could promote the transmission of arboviruses.